2018
DOI: 10.3892/ijmm.2018.3754
|View full text |Cite
|
Sign up to set email alerts
|

Efficient increase of the novel recombinant human plasminogen activator expression level and stability through the use of homozygote transgenic rabbits

Abstract: Expression efficacy of recombinant protein in current expression systems is generally low. Therefore, the expression levels of recombinant proteins in the breast milk of transgenic animals are typically low. In view of this, the present study aimed to construct homozygous transgenic rabbits with a high expression level of recombinant human plasminogen activator (rhPA) during the entire lactation period. Homozygous transgenic rabbits were obtained using an effective rhPA mammary‑specific expression vector PCL25… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
6
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
3
2

Relationship

2
3

Authors

Journals

citations
Cited by 6 publications
(9 citation statements)
references
References 39 publications
1
6
0
Order By: Relevance
“…Both the goat BLG signal peptide coding region and coding sequence of the K2 and P domains of t-PA were cloned into a mammary gland-specific expression vector. As expected, transgenic rabbits harboring the vector expressed rhPA in the milk at an average concentration of 1.28 mg/ml, and the concentration of rhPA in the whole lactation period of rabbits were stable (previously reported) [24,29]. Moreover, FAPA revealed that the purified rhPA had high fibrinolytic activity, and did not cause anaphylaxis by ASA which is essential for further therapeutic use.…”
Section: Discussionsupporting
confidence: 75%
See 2 more Smart Citations
“…Both the goat BLG signal peptide coding region and coding sequence of the K2 and P domains of t-PA were cloned into a mammary gland-specific expression vector. As expected, transgenic rabbits harboring the vector expressed rhPA in the milk at an average concentration of 1.28 mg/ml, and the concentration of rhPA in the whole lactation period of rabbits were stable (previously reported) [24,29]. Moreover, FAPA revealed that the purified rhPA had high fibrinolytic activity, and did not cause anaphylaxis by ASA which is essential for further therapeutic use.…”
Section: Discussionsupporting
confidence: 75%
“…The rhPA transgenic New Zealand White rabbit lines were generated as previously reported [24,29]. rhPA transgenic rabbits harbor a mammary gland-specific expression vector that contains an artificial cDNA.…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…Therefore, it is highly possible to improve the expression level of exogenous genes in transgenic animal mammary gland by using GH gene introduction. However, the current strategy to improve the expression level of tPA and rhPA genes in the mammary gland of transgenic animals is often to optimize the gene vector construction [15][16][26][27] . There are few reports on the synergistic promotion of tPA gene expression by double transgenic animals, especially the study of GH gene synergistically promoting the expression of tPA in transgenic animals at home and abroad.…”
Section: Discussionmentioning
confidence: 99%
“…They were mammalian mammary gland-specific expression vectors with goat β-casein as regulatory element and CMV as promoter (Fig. 1), which have been validated for expression recombinant protein on goat cells, mice, and individual rabbits [16,[26][27] . FSH (Ningbo Sansheng Pharmaceutical Co. Ltd.), HCG (Lizhu Pharmaceutical Co. Ltd.), Sumianxin II(Veterinary Institute of Military University), FBS(HyClone), hyaluronidase(Sigma), Zoletil50(Virbac), protease K(Sigma), M2(Sigma), M16 (Sigma), mouse anti-tPA monoclonal antibody (Santa Cruz), goat anti-mouse monoclonal antibody IgG-HRP(Santa Cruz); DNA gel purification and recovery kit was purchased from QIAGEN, various restriction enzymes and DNA polymerases were purchased from Takara Bio (Dalian) Co. Ltd., other reagents were purchased from Shanghai Pharmaceuticals, Shanghai Shenggong Bioengineering Co. Ltd., Nanjing Shengxing Biotechnology Co. Ltd.…”
Section: Vectors and Reagentsmentioning
confidence: 99%